Precipitation efficiency derived from isotope ratios in water vapor distinguishes dynamical and microphysical influences on subtropical atmospheric constituents. Issue 18 (19th September 2015) - Bailey, A.; Nusbaumer, J.; Noone, D.
Abstract: With water vapor and clouds expected to effect significant feedbacks on climate, moisture transport through convective processes has important implications for future temperature change. The precipitation efficiency—the ratio of the rates at which precipitation and condensation form ( e  =  P / C )—is useful for characterizing how much boundary layer moisture recycles through precipitation versus mixes into the free troposphere through cloud detrainment. Yet it is a difficult metric to constrain with traditional observational techniques. This analysis characterizes the precipitation efficiency of convection near the Big Island of Hawaii, USA, using a novel tracer: isotope ratios in water vapor. The synoptic circulation patterns associated with high and low precipitation efficiency are identified, and the importance of large‐scale dynamics and local convective processes in regulating vertical distributions of atmospheric constituents important for climate is evaluated. The results suggest that high e days are correlated with plume‐like transport originating from the relatively clean tropics, while low e days are associated with westerly transport, generated by a branching of the jet stream. Differences in transport pathway clearly modify background concentrations of water vapor and other trace gases measured at Mauna Loa Observatory; however, local convective processes appear to regulate aerosols there. Indeed, differences between observed and simulated diurnal cycles of particle number concentration indicate that precipitation scavenges aerosols and possibly facilitates new particle formation when e is high. As measurements of isotope ratios in water vapor expand across the subtropics, the techniques presented here can further our understanding of how synoptic weather, precipitation processes, and climate feedbacks interrelate. Key Points: Water vapor isotope ratios identify convective precipitation efficiency Distinct circulation patterns result in precipitation efficiency differences High precipitation efficiency is associated with aerosol scavenging